Strategies for Successful Implementation of Inclusive Education in Indonesia: A Review - Rahmi, Iftita; Damra, Hanny Rufaidah; Desvianti, Erika; Dalimunthe, Hanifa Laura (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Inclusive education has emerged as one of the most successful approaches to meeting the educational needs of students with special educational needs (SEN). However, the implementation of inclusive education still faces several challenges. This review aims to address these challenges and identify effective strategies for successfully implementing inclusive education. A total of fifteen research articles from ERIC, ProQuest, and Google Scholar published between 2020 and 2024 were included in this review. The review identified two key strategies to tackle these challenges: providing comprehensive teacher training programs and promoting the use of Universal Design Learning (UDL) in schools. These strategies have the potential to improve the quality of learning, student engagement, equal access to learning materials, and support for SEN students.